1995
DOI: 10.1007/bf00198304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine vapour inhalation on the relief of tobacco withdrawal symptoms

Abstract: Fifteen subjects participated in a randomised, placebo-controlled cross-over study to assess the effect of a nicotine vapour inhaler on craving and other withdrawal symptoms during a two-day smoking-free period. Craving and withdrawal symptoms were rated nine times over the two-day period on 10 cm visual analogue scales. Plasma nicotine concentrations in the afternoon of each study day were determined. The results show that active treatment was significantly superior to placebo in decreasing craving and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…17) Typical trough concentrations during daily smoking are 10 to 37 ng/ml, and typical peak concentrations range between 19 and 50 ng/ml. 24,[34][35][36][37] The mean increase in nicotine levels that occurs after smoking a single cigarette was 10.9 ng/ml in smokers with no smoking abstinence on the study day. 38) Our nicotine concentration data during smoking were within the range of these values, but close to the upper range.…”
Section: Discussionmentioning
confidence: 99%
“…17) Typical trough concentrations during daily smoking are 10 to 37 ng/ml, and typical peak concentrations range between 19 and 50 ng/ml. 24,[34][35][36][37] The mean increase in nicotine levels that occurs after smoking a single cigarette was 10.9 ng/ml in smokers with no smoking abstinence on the study day. 38) Our nicotine concentration data during smoking were within the range of these values, but close to the upper range.…”
Section: Discussionmentioning
confidence: 99%
“…The nicotine concentration of 3–6 mg/l is much lower than that found in the mainstream smoke of a cigarette. The descriptor “inhaler” is somewhat inappropriate since only very tiny amounts of nicotine are absorbed in the lungs14; instead nicotine is absorbed bucally like nicotine gum. Blood concentrations of nicotine resulting from use of the inhaler are typically half of that derived from cigarettes 14.…”
Section: Methodsmentioning
confidence: 99%
“…In 1995 another study by Lunell et al found that 80% of participants preferred shallower puffing for nicotine inhalers, and only 13% favored deeper inhalation [84]. They also observed that a placebo inhaler containing no nicotine resulted in partial suppression of some withdrawal symptoms such as irritability and difficulty in concentrating.…”
Section: Electronic Cigarettes (E-cigarettes)mentioning
confidence: 99%